Predicting Students’ Academic Achievement on the Patterns of Tahfidz al-Qur’an Programs in Public Universities - Mutimmatul Faidah (Edukasia Islamika : Jurnal Pendidikan Islam, 2020)
The present study reports student activities of tahfidz al-Qur’an at a public university in East Java, Indonesia, explores obstacles in enacting tahfidz programs, and examines the relationship between tahfidz activities and academic achievement. Grounded in mixed-methods, a qualitative approach was undertaken to describe patterns of tahfidz activities and problems, whereas the quantitative one was employed to measure the relationship between tahfidz activities and academic achievement. 25 students of tahfidz programs in four faculties volunteered to participate in the study. Data were collected through interviews and academic achievement documents. Study findings expose that there were three types of tahfidz students with numerous activity patterns, i.e. giving additional memorization, muraja’ah, and memorizing fluency using talaqqi-musyafahah and tasmi’-muraja’ah methods. Another result portrays that tahfidz students’ problems relied on time management, the lack of meeting intensity between students and their ustadz/teachers, the unsupported atmosphere, and the memorization method that did not optimize multiple intelligence. This study also reveals the fact that the tahfidz activities and academic achievement had a significant correlation (p < .01). It indicates that if the activities of tahfidz al-Qur’an encouraged, the student’s learning achievement would leverage as well